Pharmacological ablation of the airway smooth muscle layer—Mathematical predictions of functional improvement in asthma - Donovan, G.M.; Wang, K.C.W.; Shamsuddin, D.; Mann, T.S.; Henry, P.J.; Larcombe, Alexander; Noble, P.B. (2020)
Airway smooth muscle (ASM) plays a major role in acute airway narrowing and reducing ASM thickness is expected to attenuate airway hyper-responsiveness and disease burden. There are two therapeutic approaches to reduce ASM thickness: (a) a direct approach, targeting specific airways, best exemplified by bronchial thermoplasty (BT), which delivers radiofrequency energy to the airway via bronchoscope; and (b) a pharmacological approach, targeting airways more broadly. An example of the less well-established pharmacological approach is the calcium-channel blocker gallopamil which in a clinical trial effectively reduced ASM thickness; other agents may act similarly. In view of established anti-proliferative properties of the macrolide antibiotic azithromycin, we examined its effects in naive mice and report a reduction in ASM thickness of 29% (p <.01). We further considered the potential functional implications of this finding, if it were to extend to humans, by way of a mathematical model of lung function in asthmatic patients which has previously been used to understand the mechanistic action of BT. Predictions show that pharmacological reduction of ASM in all airways of this magnitude would reduce ventilation heterogeneity in asthma, and produce a therapeutic benefit similar to BT. Moreover there are differences in the expected response depending on disease severity, with the pharmacological approach exceeding the benefits provided by BT in more severe disease. Findings provide further proof of concept that pharmacological targeting of ASM thickness will be beneficial and may be facilitated by azithromycin, revealing a new mode of action of an existing agent in respiratory medicine.